A civil society organisation response to water service delivery issues in South Africa drives transformative praxis. Part 2: Knowledge building, learning and active citizenship. Issue 107 (December 2019) - Weaver, M.J.T; O'Keeffe, J.; Hamer, N.; Palmer, C.G
Highlights: A civil society organisation (CSO) catalysed water-related social learning. Active citizenship was more evident at an individual or group than community level. Learning and identity development occurred though sustained engagement in practice. An iterative cycle of practice and reflection promoted learning-by-doing in the CSO. Sustained support is needed for learning to lead to agency and improved livelihoods. Abstract: Human capacity growth in knowledge and innovation is crucial if South Africa is to achieve developmental goals such as efficient, sustainable and equitable water resource management. About 80 percent of the South African population comprises socially and economically disadvantaged people, living in township areas (urban areas previously allocated to Black residents during the apartheid era) that experience low household water security and lack water-related knowledge capacity. For example, the national unemployment rate is 36.3%, and in the region of the study, the Eastern Cape, is 44.5%. An integrated approach to water resource management requires meaningful participation of water stakeholders in management processes. Civil society organisations championing practices to address water service delivery issues in their local communities are well placed to build their individual capacity and foster community capacity development and active citizenship around water issues. This paper explores the learning experiences of a civil society organisation, Water for Dignity (WfD), as they addressed water service delivery issues in the Makana Local Municipality, in the Eastern Cape of South Africa. The learning process of the WfD group was explored through the retrospective analysis of data collected through participatory action research, at the WfD group, and wider community level. Learning within the WfD group was analysed through a communities of practice lens. Learning between WfD and the wider community was analysed through using a social learning lens. Learning at WfD team level occurred in four ways, through learning as belonging, learning as doing, learning as experiencing and learning as becoming. Social learning that occurred at a community level related mainly to personal water rights and best practices for improving water quality and water conservation. These were fostered mainly through structured citizen engagements offered by WfD. The research provides evidence that civil society organisations can play an important role in bridging water-related knowledge gaps and can foster active citizenship in South African communities.